Are African Households Heterogeneous Agents? : Stylized Facts on Patterns of Consumption, Employment, Income and Earnings for Macroeconomic Modelers - Fox, Louise (Washington, D.C. : International Monetary Fund, 2015)
This paper reviews the evidence on how households in Sub-Saharan Africa segment along consumption, income and earning dimensions relevant for quantitative macroeconomic policy models which incorporate heterogeneity. Key findings include the importance of home-grown food in the income and consumption of house-holds well up the income distribution, the lack of formal financial inclusion for all but the richest households, and the importance of non-wage income. These stylized facts suggest that an externally-generated macroeconomic shock and the short-term policy response would mainly affect the behavior and welfare of these richer urban households, who are also more likely to have the means to cope. Middle class and poor households, especially in rural areas, should be insulated from these external shocks but vulnerable to a wide range of structural factors in the economy as well as idiosyncratic shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet